3D Culture of Bone Marrow-Derived Mesenchymal Stem Cells (BMSCs) Could Improve Bone Regeneration in 3D-Printed Porous Ti6Al4V Scaffolds - Lingjia Yu; Yuanhao Wu; Jieying Liu; Bo Li; Bupeng Ma; Yaqian Li; Zhenfei Huang; Yu He; Hai Wang; Zhihong Wu; Guixing Qiu (Stem Cells International)
Mandibular bone defect reconstruction is an urgent challenge due to the requirements for daily eating and facial aesthetics. Three-dimensional- (3D-) printed titanium (Ti) scaffolds could provide patient-specific implants for bone defects. Appropriate load-bearing properties are also required during bone reconstruction, which makes them potential candidates for mandibular bone defect reconstruction implants. However, in clinical practice, the insufficient osteogenesis of the scaffolds needs to be further improved. In this study, we first encapsulated bone marrow-derived mesenchymal stem cells (BMSCs) into Matrigel. Subsequently, the BMSC-containing Matrigels were infiltrated into porous Ti6Al4V scaffolds. The Matrigels in the scaffolds provided a 3D culture environment for the BMSCs, which was important for osteoblast differentiation and new bone formation. Our results showed that rats with a full thickness of critical mandibular defects treated with Matrigel-infiltrated Ti6Al4V scaffolds exhibited better new bone formation than rats with local BMSC injection or Matrigel-treated defects. Our data suggest that Matrigel is able to create a more favorable 3D microenvironment for BMSCs, and Matrigel containing infiltrated BMSCs may be a promising method for enhancing the bone formation properties of 3D-printed Ti6Al4V scaffolds. We suggest that this approach provides an opportunity to further improve the efficiency of stem cell therapy for the treatment of mandibular bone defects.